PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DIREKTORAT PENGEMBANGAN SATUAN PERMUKIMAN DAN PUSAT SATUAN KAWASAN PENGEMBANGAN (PSP & PSKP) KEMENTERIAN DESA, PDT DAN TRANSMIGRASI - Purnawan, Subiyanto; Ratnawati, Whina (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of work discipline and work motivation on employee performance at the Directorate of Settlement Unit Development and the Center for Development Area Units of the Ministry of Villages, Development of Disadvantaged Regions and Transmigration. The sample used was a saturated sampling technique, totaling 90 employees. Data collection techniques through primary and secondary data. Data analysis techniques use descriptive statistics, validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and f test with the help of the Statistical Product and Service Solution (SPSS) program ). The research results show that: (1) Partially there is a positive and significant influence between work discipline on employee performance, this is proven by the calculated t value of 4.723 > t table 1.98761 with a significance of 0.000 < 0.05. (2) Partially there is a positive and significant influence between work motivation on employee performance, this is proven by the calculated t value of 2.430 > t table 1.98761 with a significance of 0.017 < 0.05. (3) Simultaneously there is a positive and significant influence between work discipline and work motivation on employee performance, this is proven by the calculated f value of 22.255 > f table 3.10 with a significance level of 0.000 < 0.05..